Poetry and listening : the noise of lyric - Skoulding, Zoë (Liverpool University Press, 2020)
At the intersection between sound studies and new lyric criticism, this book explores the social, political and ecological dimensions of contemporary poetry's acoustic contexts. It discovers how poetry in the UK and USA has been re-energised by the influence of recorded sound and the creative methods that emerged with it.
Keywords: Poetics.; Listening (Philosophy); English poetry -- History and criticism.; American poetry -- History and criticism.; Literature -- Philosophy.; Poétique.; Écoute (Philosophie); Poésie anglaise -- Histoire et critique.; Poésie américaine -- Histoire et critique.; Literature -- Philosophy; American poetry; English poetry; Poetics; Criticism, interpretation, etc.